Neonatal androgenization of hypogonadal (hpg) male mice does not abolish estradiol-induced FSH production and spermatogenesis - Kerr Jeffrey B; Baines Helen; Nwagwu Margaret O; Ebling Francis JP (BMC, 2005)
Abstract Background Testicular development is arrested in the hypogonadal (hpg) mouse due to a congenital deficiency in hypothalamic gonadotropin-releasing hormone (GnRH) synthesis. Chronic treatment of male hpg mice with estradiol induces FSH synthesis and secretion, and causes testicular maturation and qualitatively normal spermatogenesis. As estradiol negative feedback normally inhibits FSH production in the male, this study tested whether this paradoxical response to estradiol in the male hpg mouse might be due to inadequate masculinisation or incomplete defeminization in the neonatal period. Previous studies have demonstrated that treatment of hpg mice with testosterone propionate in the immediate neonatal period is necessary to allow full reproductive behaviors to be expressed following suitable endocrine stimulation at adult ages. Methods Hpg mice were treated with 100 μg testosterone propionate or vehicle on postnatal day 2. At 35 days of age, subgroups of these mice were treated with silastic implants containing estradiol or cholesterol. Reproductive behavior was scored in tests with steroid-primed female mice, then testicular development was assessed histologically, and measures of pituitary FSH content made at 85 days of age. Results The neonatal testosterone propionate treatment successfully defeminized female litter mates, as revealed by impaired vaginal opening and deficiencies in lordosis behavior, and it allowed appropriate male reproductive behavior to be expressed in a proportion of the hpg males when tested at an adult age. However, neonatal androgen supplementation did not block or even reduce the subsequent actions of estradiol in increasing pituitary FSH content, nor did it affect the ability of estradiol to induce qualitatively normal spermatogenesis. Conclusion The ability of the hpg male to show a "female" neuroendocrine response to estradiol is not a result of inadequate androgenization during neonatal development, and thus the actions of estradiol revealed in this rodent model are not an artefact of incomplete sexual differentiation, but reflect a physiological role of estradiol occurring during a specific early temporal window of male reproductive development.